1998
DOI: 10.1523/jneurosci.18-11-04022.1998
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Neuronal Activity by Glial Cells in the Retina

Abstract: Glial-neuronal communication was studied by monitoring the effect of intercellular glial Ca 2ϩ waves on the electrical activity of neighboring neurons in the eyecup preparation of the rat. Calcium waves in astrocytes and Mü ller cells were initiated with a mechanical stimulus applied to the retinal surface. Changes in the light-evoked spike activity of neurons within the ganglion cell layer occurred when, and only when, these Ca 2ϩ waves reached the neurons. Inhibition of activity was observed in 25 of 53 neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
254
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 348 publications
(263 citation statements)
references
References 28 publications
9
254
0
Order By: Relevance
“…The effect of these activated glial cells on neurons has been assessed by recording the light-evoked spike activity of a nearby ganglion cell with an extracellular microelectrode (Newman and Zahs, 1998). We found that stimulated glial cells either enhance or depress light-evoked neuronal activity (Fig.…”
Section: Glia To Neuron Signalingmentioning
confidence: 98%
“…The effect of these activated glial cells on neurons has been assessed by recording the light-evoked spike activity of a nearby ganglion cell with an extracellular microelectrode (Newman and Zahs, 1998). We found that stimulated glial cells either enhance or depress light-evoked neuronal activity (Fig.…”
Section: Glia To Neuron Signalingmentioning
confidence: 98%
“…The bar at the bottom shows the repetitive light stimulus that evoked neuronal spiking. Reproduced with modification from Newman and Zahs (1998). Glial modulation of synaptic transmission by glutamate transport and release of D-serine.…”
Section: Future Directions and Implicationsmentioning
confidence: 99%
“…Interestingly, mechanical stimulation of a single astrocyte leads to a propagating calcium wave involving both astrocytes and Muller cells in the intact adult retina. These glial waves modulate the firing rate of retinal neurons, presumably by release of glutamate from the glial cells (Newman and Zahs, 1998). …”
Section: Possible Physiologic Roles For Nachrs On Nonexcitable Cellsmentioning
confidence: 99%